The Sandman. Vol. 5, A game of you - Gaiman, Neil (Gaiman, Neil. Sandman library, 1993)
Take an apartment house, mix in a drag queen, a lesbian couple, some talking animals, a talking severed head, a confused heroine, and the deadly Cuckoo. Stir vigorously with a hurricane and Morpheus himself and you get this fifth installment of the Sandman series. This story stars Barbie, who first makes an appearance in The Doll's House, who here finds herself a princess in a vivid dreamworld.